IMPLEMENTATION OF WIRELESS CONTROLLER USING CAPSMAN (CONTROLLER ACCESS POINT SYSTEM MANAGER) IN COMPUTER LABORATORY OF SMK NEGERI 9 MEDAN - Muhammad Donni Lesmana Siahaan; Iskandar Iskandar (INFOKUM, 2022)
In facilitating network configuration and user devices that are very often used are proxy. Because in proxy it is very easy to operate when compared to other routers. Basically, in Mikrotik, there are several features, including Capsman (Controller Access Point System Manager), which is a wireless controller feature to make it easier to centrally manage all wireless access point devices on the network. Setting up the network centrally Wireless AP Mikrotik will make it easier for operators to operate or manage the network, so that the configuration is only network speed traffic based on distance by limiting the user's distance using the Capsman facility, and monitoring more easily using the proxy and can minimize unused bandwidth so that can be used in rooms that are active in the internet network.